Tyrosine 7.43 is important for mu-opioid receptor downstream signaling pathways activated by fentanyl - Tian, Xiangyun; Zhang, Junjie; Wang, Shaowen; Gao, Huan; Sun, Yi; Liu, Xiaoqian; Fu, Wei; Tan, Bo; Su, Ruibin (Frontiers in Pharmacology, 2022)
G protein-coupled receptors (GPCRs) can signal through both G proteins and β-arrestin2. For the μ-opioid receptor (MOR), early experimental evidence from a single study suggested that G protein signaling mediates analgesia and sedation, whereas β-arrestin signaling mediates respiratory depression and constipation. Subsequently, receptor mutations were used to clarify which residues interact with ligands to selectively regulate signals in a ligand-specific manner. However, there is no systematic study on how to determine these residues and clarify the molecular mechanism of their influence on signal pathways. We have therefore used molecular docking to predict the amino acid sites that affect the binding of ligands and MOR. Then the corresponding sites were mutated to determine the effect of the structural determinant of MOR on Gi/o protein and β-arrestin pathways. The pharmacological and animal behavioral experiments in combination with molecular dynamics (MD) simulations were used to elucidate the molecular mechanism of key residues governing the signaling. Without affecting ligand binding to MOR, MORY7.43A attenuated the activation of both Gi/o protein and β-arrestin signaling pathways stimulated by fentanyl, whereas it did not change these two pathways stimulated by morphine. Similarly, the activation peak time of extracellular regulated protein kinases (ERK) was significantly prolonged at MORY7.43A compared to MORwildtype stimulated by fentanyl, but there was no difference stimulated by morphine. Additionally, MORY7.43A significantly enhanced analgesia by fentanyl but not by morphine in the mice behavioral experiment. Furthermore, the MD simulations showed that H6 moves toward the cellular membrane. H6 of fentanyl-Y7.43A system moved outward more than that in morphine-Y7.43A system. Y7.43 mutation disrupted hydrophobic interactions between W6.48 and Y7.43 in fentanyl-Y7.43A system but not morphine-Y7.43A system. Our results have disclosed novel mechanisms of Y7.43 mutation affecting MOR signaling pathways. Y7.43 mutation reduced the activation of Gi/o protein pathway and blocked the β-arrestin2 recruitment, increased the H6 outward movement of MOR and disrupted hydrophobic interactions. This may be responsible for the enhanced fentanyl analgesia. These findings are conducive to designing new drugs from the perspective of ligand and receptor binding, and Y7.43 is also expected to be a key site to structure optimization of synthesized compounds.